Molecular characterization and recombinant gonadotropin subunit development for improving reproductive performance in female Hemibagrus nemurus valenciennes - Mohamed Zulperi, Zarirah (2016)
Hemibagrus nemurus, locally known as ‘ikan baung’, is a valuable cultured catfish in Malaysia, but the production is limited due to problems associated with its reproduction. Most hatcheries encountered problems in induced spawning due to the fact that the fish do not expose to their natural spawning habitat, especially the failure of female brood stock to undergo final oocyte maturation (FOM), preventing its ability to ovulate and spawn. Gonadotropin (GtH), comprised of follicle-stimulating hormone (FSH) and luteinizing hormone (LH), play an important role in gametogenesis and sexual maturation in mammals as well as in fish. This research was conducted to study the molecular characterization and to monitor changes in the mRNA expression of three GtH subunits, , FSH, and LH, during the reproductive cycle of the female H. nemurus. Next, a single-chain recombinant LH (rLH) of H. nemurus was expressed using E. coli expression system. The bioactivity of the recombinant hormone was assessed for their potency in stimulating the production of 17-estradiol (E2), ovarian development and mRNA expression level of GtH subunits in experimental fish. Molecular characterization using PCR amplifications revealed that the cDNA of , FSH and LH in H. nemurus were 656, 728 and 602 bp, and encoded for 116, 134 and 140 amino acids, respectively. Multiple sequence alignment showed all the three subunits shared the highest homology with Siluriformes and Anguilliformes, and least similar to higher vertebrates. Phylogenetic analysis of  and FSH grouped fishes and higher vertebrates together, while in LH, the tree was divided in two distinct groups, the first group contained all fishes together, and the second group only contained higher vertebrates. The abundance of transcripts encoding the GtH subunits, , FSH and LH subunits in pituitaries of female H. nemurus was tracked throughout the reproductive cycle using quantitative real-time PCR. Data were collected from August 2013 until October 2015, with fish aged between 1 to 27 month-old. The mRNA expression of GtH subunits increased together with ovarian development throughout the reproductive cycle. The FSH mRNA level increased during ovarian development and reached its peak in mid-vitellogenesis and reduced during ovulation and spawning, whereas the LH mRNA level significantly increased (P<0.05) in late vitellogenesis and reached its peak during ovulation and spawning period. In  subunit, the mRNA level corresponded to FSH and LH, which showed its highest expression during ovulation. This suggest that FSH could be involved in vitellogenesis, while LH subunit raised at the end of reproductive cycle, determined the involvement of LH in ovulation and final oocyte maturation. A single chain recombinant LH (rLH) from H. nemurus consisted of LHβα fusion proteins was constructed and derived through gene-synthesis. The rLH construct was successfully cloned into pET-32 Ek/LIC and expressed in E. coli BL21 (DE3) cells. A specific band at 45.4 kDa was detected which corresponded to the molecular size of fusion rLH resolved by SDS PAGE. Two monoclonal antibodies, His-Tag and S-tag, were used to confirm the same expressed bands in Western immunoblotting. In order to investigate the bioactivity of the rLH hormone, fish trial was performed to assess the effect of exogenous rLH on the plasma level of E2, their mRNA level of GtH subunits and oocyte development in the gonad of female H. nemurus. Immature female H. nemurus were divided into four different treatments of ten fish/group, and each group received a single injection of: Group 1= 1X PBS (sham control), Group 2= 0.5 ml/kg Ovaprim (positive control), Group 3= rLH 50 g/kg, and Group 4= rLH 150 g/kg, respectively. Study parameters including the oocyte development through observation on gonad histology, the E2 plasma levels using enzyme-linked immunosorbent assay (ELISA) and the mRNA transcript level of , FSH and LH subunits using real-time PCR. Based on the histological observation of the gonad, fish received treatment with rLH 50 g/kg, rLH 150 g/kg, as well as Ovaprim were able to induce the maturation of oocyte after 48 hr p.i. The E2 plasma level in fish treated with rLH 50 g/kg raised after 6 hr p.i., significantly increased (p<0.05) after 12 hr p.i., and the level was sustained up to 24 hr p.i. The mRNA expression levels of , FSH and LH also showed significant increment (p<0.05) in fish treated with rLH 50 g/kg after 48 hr p.i. Fish treated with Ovaprim showed significant increased (p<0.05) of E2 plasma level after 6 hr p.i., but the level was reduced after 12 hr p.i. There was no significant increased (p>0.05) of mRNA subunits in fish treated with Ovaprim after 48 hr p.i., as compared to sham control fish. Meanwhile, treatment with rLH 150 g/kg showed a weak stimulatory effect on the E2 production and mRNA transcript level of GtH subunits. The results revealed that treatment with rLH at 50 g/kg is the best dosage to induce spawning and oocyte maturation in maturing female H. nemurus. These findings enhanced the understanding of GtH subunit in H. nemurus, and the temporal profile helped to estimate the correct time for hormonal therapies to induce ovulation and spawning in female H. nemurus reared in captivity. The production of recombinant GtH from H. nemurus would offer the establishment of a potentially efficient method to induce the gonadal development in this species and possibly in other catfish species.